New chemical constituent from the rhizomes of Johannesteijsmannia altifrons - Noor Aziiraa Sabri,; W.A. Yaacob,; Nur Shafiqa Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A new compound namely 2-[(1′E)-3′-hydroxyl-1′-methyl-1′-propen-1′-yl]-6-methoxy-7-[(2′′-methylheptyl)oxy]-5-benzofurancarboxylic acid and three known compounds of β-sitosterol, γ-taraxasterol and stigmasterol were isolated from the n-hexane extracts of the rhizomes and fruits of Johannesteijsmannia altifrons using vacuum liquid, column and radial chromatography. The structures of the isolated compounds were determined by means of 1D and 2D NMR, FT-IR, UV-VIS spectroscopy and mass spectrometry.